Heat Transfer, Knock Modeling and Cyclic Variability in a "Downsized" Spark-Ignition Turbocharged Engine (Advances in Applied Mathematics and Mechanics, 2021)
In the present paper a combined procedure for the quasi-dimensional modellingof heat transfer, combustion and knock phenomena in a "downsized" Spark Ignitiontwo-cylinder turbocharged engine is presented. The procedure is extended to alsoinclude the effects consequent the Cyclic Variability. Heat transfer is modelledby means of a Finite Elements model. Combustion simulation is based on a fractaldescription of the flame front area. Cyclic Variability (CV) is characterized throughthe introduction of a random variation on a number of parameters controlling therate of heat release (air/fuel ratio, initial flame kernel duration and radius,laminar flame speed, turbulence intensity). The intensity of the random variationis specified in order to realize a Coefficient Of Variation (COV) of the  IndicatedMean Effective Pressure (IMEP) similar to the one measured during an experimentalcampaign. Moreover, the relative importance of the various concurring effects isestablished on the overall COV. A kinetic scheme is then solved within the unburnedgas zone, characterized by different thermodynamic conditions occurring cycle-by-cycle.In this way, an optimal choice of the "knock-limited" spark advance is effected andcompared with experimental data. Finally, the CV effects on the occurrence ofindividual knocking cycles are assessed and discussed.